THE EFFECT OF MENU DESIGN ON CUSTOMER PURCHASE INTENTION: A CASE STUDY OF ‘WAROENG MAS KEMAL’ RESTAURANT - Fikri, Mas Kemal Rausyan; Ramadhan, Ahmad Seiichi (Journal of Business Strategy and Execution, 2011)
The purpose of this study is to investigate whether the elements of menu design have a significant effect on customer purchase intention in Waroeng Mas Kemal Restaurant, thus providing better comprehension regarding the implementation of menu design elements related to customer purchase intention. The study employs a questionnaire as the main data collection, which addressed the customers who ate at Waroeng Mas Kemal Restaurant within a two month period. The questionnaire contains questions and statements regarding the customers’ general information, as well as their opinion towards the menu design. The gathered data was later analyzed using multiple regressions technique. Purchase intention is affected by menu design variables, in which the menu’s cover design has the highest contribution, followed by font style and description. Meanwhile, pictures and sizes do not have any effect towards customer purchase intention. The study suggests, the restaurant management need to develop better menu design, especially focusing on the menu’s cover design, font style and description in order to increase sales and profits for their restaurant.